WASTE MANAGEMENT IN THE TOURISM INDUSTRY: A SYSTEMATIC REVIEW - Terdznan Tansel, (Academic Journal of Physical and Chemical Sciences, 2019)
One of the important issue in the world is waste and recycling management. Considering the pollution, economic and social damages, the reduction of natural resources caused by the wastes, the effective management and recycling of the wastes have impact on the operational efficiencies and the effective management and recycling of waste are important in ensuring sustainable development and productivity for enterprises. The tourism industry can be seen as a natural laboratory for waste management and recycling within the scope of its products and services. Recent years, it has been observed that there has been an increasing study on waste management and recycling; however, there is a limited study on the tourism industry. Therefore, the main purpose of the study is to review the waste management studies in the tourism industry by systematic review technique. For this purpose, 15 articles published in the Web of Science (WOS) since 1975 have been examined. The results were evaluated and suggestions were given for future researches within the scope of the tourism industry.